Modulation of monocytes by bioactive lipid anandamide in multiple sclerosis involves distinct Toll-like receptors. (November 2016) - Chiurchiù, Valerio; Leuti, Alessandro; Cencioni, Maria Teresa; Albanese, Maria; De Bardi, Marco; Bisogno, Tiziana; Centonze, Diego; Battistini, Luca; Maccarrone, Mauro
Graphical abstract: Abstract: Monocytes are believed to be involved in the immunopathogenesis of multiple sclerosis (MS). The aim of this study was to investigate their role in MS and their immunomodulation by the endocannabinoid system (ECS), a novel target for the treatment of this disease. We compared the level of cytokine production from monocytes in healthy subjects and MS patients upon stimulation with viral or bacterial Toll-like receptors (TLR) and we evaluated the ECS immunomodulatory role in these cells. Here we show that MS monocytes produced more TNF-α, IL-12 and IL-6 following activation of TLR2/4 with LPS or of TLR5 with flagellin, as opposed to TLR7/8 stimulation with R848. Furthermore AEA, the main endocannabinoid, suppressed cytokine production and release from healthy monocytes upon stimulation with both bacterial and viral TLR receptors but not in cells from MS patients, where its immunosuppressive activity was TLR7/8-dependent. Altered expression levels of key ECS members in MS monocytes paralleled these data. Our data disclose a distinct immunomodulatory effect of AEA and an alteration of AEA-related members of the ECS in monocytes from MS patients that involves viral but not bacterial TLR. These findings not only may help to better understand the role of monocytes in MS immunopathogenesis but also could be of help to exploit new endocannabinoid-based drugs that target innate immune cells.